2021
DOI: 10.1029/2021jc017995
|View full text |Cite
|
Sign up to set email alerts
|

The Observed Agulhas Retroflection Behaviors During 1993–2018

Abstract: The Agulhas Current (AC)-the subtropical western boundary current of the Southern Indian Ocean (e.g., Imawaki et al., 2013;Lutjeharms, 2006)-flows poleward along the eastern coast of South Africa with a mean volume transport up to 84 Sv (1 Sv = 10 6 m s −3 ) and the maximum surface velocity exceeding 2 m s −1 (Beal & Bryden, 1999;Beal et al., 2015). Upon reaching the southern tip of the African continent, the AC departs from the coast, with its main body looping back to feed the eastward-flowing Agulhas Return… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 65 publications
1
4
0
Order By: Relevance
“…The CESM-derived W Wind reveals negative centers around the AR regime (figure 4(a)), indicative of pronounced wind stress, responsible for damping mesoscale eddies within the AR region. These zones correlate closely with eddy-shedding positions in the 10 • E-23 • E range (Zhu et al 2021), which are characterized by high EKE levels. Specifically, eddy-wind interaction in the upstream and downstream zones account for ∼12% and ∼36% of the total EKE dissipation, respectively.…”
Section: Potential Role Of Eddy-wind Interactionsupporting
confidence: 63%
See 3 more Smart Citations
“…The CESM-derived W Wind reveals negative centers around the AR regime (figure 4(a)), indicative of pronounced wind stress, responsible for damping mesoscale eddies within the AR region. These zones correlate closely with eddy-shedding positions in the 10 • E-23 • E range (Zhu et al 2021), which are characterized by high EKE levels. Specifically, eddy-wind interaction in the upstream and downstream zones account for ∼12% and ∼36% of the total EKE dissipation, respectively.…”
Section: Potential Role Of Eddy-wind Interactionsupporting
confidence: 63%
“…The oceanic mesoscale eddy signals are associated with temporal scales of 30-270 d in the AC system (Zhu et al , 2021. In this study, the cutoff period is set to 260 d between the mean flow and mesoscale eddies, and 30 d between mesoscale eddies and highfrequency processes, respectively.…”
Section: Multiscale Energy and Vorticity Analysis (Ms-eva) Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A large number of previous studies have shown much interest in the Agulhas retroflection position, as it is, on one side, affected by the upstream dynamical processes and, on the other, regulates the allocation ratio of Agulhas leakage to ARC [10,[15][16][17][18]. The variability of the retroflection can also have an impact on the local climate [19]. However, the Agulhas retroflection point itself is restrained by the bottom topography as well as local and large-scale wind patterns [13,20].…”
Section: Introductionmentioning
confidence: 99%